Factors associated with possession of accurate knowledge regarding occupational health management among operations leaders of radiation decontamination workers in Fukushima, Japan: a cross-sectional study. Issue 5 (5th May 2019) - Hidaka, T; Kakamu, T; Endo, S; Kasuga, H; Masuishi, Y; Kumagai, T; Sato, S; Sasaki, T; Fukushima, T
Abstract : Objectives: An operations leader (OL) takes an important role in occupational health management for radiation decontamination workers in Japan, and candidates for the position must participate in a training session to acquire the necessary knowledge as required by law. However, it has not been clarified whether the candidates for the OL position actually possess accurate knowledge regarding occupational health management for such work after the training session. We, therefore, aimed at examining the current occupational health management knowledge among the candidates and investigating factors related to the knowledge, with hypothesis that possession of accurate knowledge is associated with prior experience of having worked in radiation decontamination. Design: A cross-sectional study. Setting: The training sessions held by Fukushima Prefecture Labor Standard Associations in Fukushima, Japan, in 2017. Participants: Eighty male candidates participated in the training sessions. Outcome: The number/proportion of correct answers to the questions regarding occupational health management, such as those on working environment management, control of operations and health management. Results: The proportion of those who possessed accurate knowledge regarding working environment management, control of operations and health management was 68.8%, 55.0% and 51.2%, respectively. Experience of radiation decontamination work was associated with the possession of inaccurate knowledge regarding working environment management (OR 0.140 (95% CI 0.042 to 0.464)), and the uncertainty of future radiation decontamination work schedules in difficult-to-return zones was associated with the possession of accurate knowledge regarding health management (OR 4.344 (95% CI 1.509 to 12.50)). Conclusions: Previous experience in radiation decontamination work may hinder the ability to acquire accurate information regarding working environment management among candidates for an OL position. To promote adequate occupational health management for radiation decontamination workers, it is required to establish an effective instructional method for the OL candidate training sessions with consideration of previous relevant experience.